2022
DOI: 10.1186/s41938-021-00500-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification and virulence of indigenous entomopathogenic fungal strains against the peach-potato aphid, Myzus persicae Sulzer (Hemiptera: Aphididae), and the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae)

Abstract: Background As different biogeographic strains and isolates of entomopathogenic fungi vary in their genetic, enzymatic and pathogenic characteristics, this study assessed the virulence of 2 indigenous strains of Beauveria bassiana (Balsam) Vuillemin and Metarhizium anisopliae (Metschn.) Sorokin (Ascomycota, Hypocreales: Clavicipitaceae), isolated from naturally infected insect cadavers, against the 3rd instar nymphs of Myzus persicae (Sulzer) (Hemiptera: Aphididae) and 3rd instar larvae of Spodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Metarhizium anisopliae (Deuteromycotina: Hyphomycetes) (Sahayaraj & Borgio Francis, 2010) and Lecanicillium longisporum (Ascomycota: Hypocreomycetidae) (Rachel et al, 2009) are commercially used as a biological control agent against various insect pests. Many previous studies have found that M. anisopliae was a promising biocontrol agent on various hemipteran pests such as Bactericera cockerelli (Hemiptera: Triozidae), Lygus lineolaris (Hemiptera: Miridae), Blissus antillus (Hemiptera: Lygaeidae) and Myzus persicae (Hemiptera: Aphididae) (Lacey et al, 2011;Houping et al, 2002;Samuels et al, 2002;Ullah et al, 2022). Similarly, L. longisporum also reported effectiveness against the following hemipterans viz., Planococcus citri (Hemiptera: Pseudococcidae) and Cinara pini (Hemiptera: Lachnidae) (Ghaffari et al, 2017;Nazemi et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…Metarhizium anisopliae (Deuteromycotina: Hyphomycetes) (Sahayaraj & Borgio Francis, 2010) and Lecanicillium longisporum (Ascomycota: Hypocreomycetidae) (Rachel et al, 2009) are commercially used as a biological control agent against various insect pests. Many previous studies have found that M. anisopliae was a promising biocontrol agent on various hemipteran pests such as Bactericera cockerelli (Hemiptera: Triozidae), Lygus lineolaris (Hemiptera: Miridae), Blissus antillus (Hemiptera: Lygaeidae) and Myzus persicae (Hemiptera: Aphididae) (Lacey et al, 2011;Houping et al, 2002;Samuels et al, 2002;Ullah et al, 2022). Similarly, L. longisporum also reported effectiveness against the following hemipterans viz., Planococcus citri (Hemiptera: Pseudococcidae) and Cinara pini (Hemiptera: Lachnidae) (Ghaffari et al, 2017;Nazemi et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…The results showed that this strain (KNU‐Ye‐1) was identical to the M. rileyi KNU‐Gunwi 2 B strain, previously identified in soil samples from Korea (Moe et al, 2021). Recent studies have reported the identification and virulence of M. rileyi against invaded FAW in various Asian countries, including China (Zhou et al, 2020), India (Shylesha et al, 2018), Pakistan (Ullah et al, 2022), and the Philippines (Montecalvo et al, 2022). To our knowledge, this is the first report of a native strain of M. rileyi infestation of S. frugiperda in a corn field in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, local parasitoids from these families have already been reported in Mexico and in several African countries; consequently, these parasitoids can help to keep this pest under control in the Old World (Koffi et al, 2020). Regarding entomopathogenic fungi, Metarhizium anisopliae (Mechnikov) Sorokin can cause a 43-100% mortality in third-instar larvae of S. frugiperda (Ullah et al, 2022b;Munywoki et al, 2022) and a 70-100% mortality in nymphae and adults of S. p. piceifrons. Additionally, it can cause mortality in others species of the Acrididae family, including Melanoplus sanguinipes Fabricius (Barrientos-Lozano et al, 2021;Dakhel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%